OLD AGE REPRESENTATION (DECREASE AND GROWTH MODELS) - Moñivas, Agustín (Anales de Psicología / Annals of Psychology, 1998)
Our knowlege about old age is a finite representation of one aspect of reality -aging as a process of the life cycle along all its dimensions-assumed to be finite. Science, developed and based on the scientific method, is just one approched to knowledge. The scientific method is any method that respect the objetivity, intelligibility and dialectic principles (we are being dialectic when we take the risk of having our knowledge knocked down by experience). Moreover, science, as an element of culture, must take the latter as a variable. From this perspective, and drawing inspiration from professor Forteza’s work (1993), cognitive and social representations implicit in everyday Psychology and scientific theories are analyzed. We raise questions concerning the reason why the decrease models have prevailed despite development means not only growth and decline but also optimization and adaptability to t he degree of competence along one’s course of life. Finally, we make a critique of the theoretical approach of successful aging, as success is still defined, to a great extent, by what the theories prescrib.